Studi Literature Review: Pentingnya Bahasa Indonesia Baku di Era Dominasi Bahasa Gaul Pada Remaja - Anggina Zahra Salsabilla; Usiono Usiono (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Adolescent language has undergone major changes over time, with slang changing the use of standard Indonesian. This causes teenagers to be less aware of the importance of using standard Indonesian as a national identity and professional communication tool. The purpose of this study is to improve adolescents' understanding of the use of standard Indonesian in academic and social contexts. The method used was to review literature from various scientific sources to look at patterns of language use, factors causing the dominance of slang, and strategies to encourage the use of standardized language. The results show that the development of social media, the surrounding environment, and the dominance of mass media slang affect the low use of standard Indonesian. The perception that standardized language is too rigid also exacerbates this. To improve standard language habits, strategic actions such as language teaching in educational institutions, language regulations, and the active role of families are needed. The results of this study are expected to raise adolescents' awareness of the importance of using official Indonesian as an effective way to communicate and mark their national identity.